Mechanisms for Settling Disputes Relating to Electronic Consumer Contracts - Dr. LAOUAREM Mohamed; Dr. TIGRINE Zahira; Dr. GUERRA Fares (Journal of the West, 2026)
Electronic consumer contracts raise numerous legal issues, which prompted the Algerian legislator to enact substantive rules aimed at protecting the electronic consumer in the digital environment. However, the enactment of substantive rules for consumer protection in electronic contracts is no longer sufficient on its own unless accompanied by procedural mechanisms that embody this protection in reality. Accordingly, this paper will address, in the first section, the rules of judicial jurisdiction as an important mechanism for settling disputes arising from electronic consumer contracts, while the second section will be devoted to electronic arbitration as an effective mechanism for settling disputes relating to electronic consumer contracts.